(untitled) (Bangladesh Journal of Physiology and Pharmacology, 2014)
Background: Infertility has become a global health problem in the world wide affecting 8-10% of couple. It is also a matter of social injustice and inequality. Increase level of insulin has been implicated as a cause of infertility. Objective: To find out the association of fasting serum insulin level with gonadotropins in infertile women. Methods: This cross sectional study was conducted in the department of Physiology, Dhaka Medical College, Dhaka from July 2010 to June 2011. A total number of 150 female age ranged from 20 40 years were included in this study. Out of them100 infertile women were selected as study group (group B). Group B was subdivided into group B1 and B2. Group B1 consisted of 50 primary infertile women and group B2 consisted of 50 secondary infertile women. Rest 50 age matched apparently healthy parous women were considered as base line control group A. All the study subjects were selected from out patient department of infertility unit, BSMMU, Dhaka. The control subjects were selected by personal contact. Serum fasting insulin was measured by enzyme-link-immunosorbend assay. Fasting blood glucose and blood glucose two hours after breakfast were measured by glucose oxidase method. The Data were collected in a prescribed data sheet after taking written consent. Statistical analyses were done by unpaired students t tests by SPSS program version 12. The level of significance was calculated and p value <0.05 was accepted as level of significance. Results: In this study, the mean fasting serum insulin level were significantly higher in infertile women than those of fertile women (p<0.001). Within the study group serum fasting insulin was higher in primary infertile women than that of secondary infertile women both were statistically not significant. Again, serum FSH and LH levels were significantly lower (P<.0001) in infertile women than those of fertile women. But serum FSH level was lower and LH level was higher in primary infertile women than that of secondary infertile women. In addition, fasting blood glucose level was almost similar but within normal limits in all groups. Blood glucose 2HABF was significantly higher in secondary infertile women than that of fertile women but within in normal limit. Moreover, fasting serum insulin level was negatively correlated with serum FSH and LH in primary infertility but negatively correlated with serum FSH and positive correlation with serum LH in secondary infertility. Conclusion: From the above study it may be concluded that fasting serum insulin level was higher in infertile women than those of healthy fertile women. These alterations may lead to menstrual irregularities, ovulatory dysfunction and infertility. http://dx.doi.org/10.3329/bjpp.v29i1-2.20063 Bangladesh J Physiol Pharmacol 2013; 29(1&2) : 17-24